Comparison Of Fractional Order PID Controller And Sliding Mode Controller With Computational Tuning Algorithm - Ghazali, Rozaimi; Chong, Shin Horng; Chong, Chee Soon; Yusof, Ahmad Anas; Chai, Mau Shern; Md Sam, Yahaya; Yusof, Ahmad Anas (Horizon Research Publishing, 2019)
The industry processes involving punching, lifting, and digging usually require high precision, high force and long operating hours that increase the prestige in the usage of the electrohydraulic actuator (EHA) system. These processes with the companion of the EHA system usually possess high dynamic complexities that are hard to be controlled and require well-designed and powerful control system. Therefore, this paper will involve the examination of the designed controllers which is applied to the EHA system. Firstly, the conventional proportional-integral-derivative (PID) controller which is the famous controller in the industry is designed. Then, the improved PID controller, which is known as the fractional order PID (FO-PID) controller is designed. After that, the design of the gradually famous robust controller in the education field, which is the sliding mode controller (SMC) is performed. Since the controller’s parameters are essentially influencing the performance of the controller, the meta-heuristic optimization method, which is the particle swarm optimization (PSO) tuning method is applied. The variation in the system’s parameter is applied to evaluate the performance of the designed controllers. Referring to the outcome analysis, the increment of 59.3% is obtained in the comparison between PID and FOPID, while the increment of 67.13% is obtained in the comparison of the PID with the SMC controller. As a conclusion, all of the controllers perform differently associated with their own advantages and disadvantage